SOME MARINE SPONGES OF NORTHEAST BRAZIL - Johnson, Marion Fischel (Arquivos de Ciências do Mar, 2018)
The Porifera in this study, with the exception of one specimen, are described from dry material collected over a period of several years by various individuais. No records are available concerning the color or consistency of the living specimens, or in some cases, the depth from which the sponge was taken. Many of the specimens were incomplete and often only one sample of a particular species was retained. Thus, in most cases, the sponges received only a tentative identification.